2015
DOI: 10.1088/1674-1056/24/7/070503
|View full text |Cite
|
Sign up to set email alerts
|

Compression and stretching of ring-vortex solitons in a bulk nonlinear medium

Abstract: Compression and stretching of ring-vortex solitons in a bulk nonlinear mediumLai Xian-Jing(来娴静) a)b) † , Cai Xiao-Ou(蔡晓鸥) b) , and Zhang Jie-Fang(张解放) a)c)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Nonlinear evolution equations can be used to describe nonlinear phenomena and play a vital role in many fields [1][2][3][4]. Nonlinear science involves the related fields of natural sciences and social sciences, mainly including mathematics, medical chemistry, biology, astronomy, physics, economics and other important subject areas, which is to construct the connection between mathematics and other disciplines.…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear evolution equations can be used to describe nonlinear phenomena and play a vital role in many fields [1][2][3][4]. Nonlinear science involves the related fields of natural sciences and social sciences, mainly including mathematics, medical chemistry, biology, astronomy, physics, economics and other important subject areas, which is to construct the connection between mathematics and other disciplines.…”
Section: Introductionmentioning
confidence: 99%
“…The interactions between optical solitons have always been attracting attention in the field of nonlinear optics since the interactions present lots of novel and fascinating phenomena such as soliton fusion, fission, and annihilation, as well as spiraling. [1][2][3][4][5][6][7][8] Wang et al investigated numerically the propagation and interactions of Airy-Gaussian beams in a cubicquintic nonlinear medium, and found that soliton pairs can be obtained by adjusting the phase shift and interval between two Airy-Gaussian beams. [9] Lan et al proposed a general propagation lattice Boltzmann model for a variable-coefficient compound Korteweg-de Vries-Burgers equation by selecting an equilibrium distribution function and adding a compensation function, and simulated the two-soliton solution by taking appropriate free parameters.…”
Section: Introductionmentioning
confidence: 99%
“…It is also relevant to refer to recent works addressing ring-and elliptic-shaped vortex solitons in relevant physical configurations. The compression and stretching of ring vortices in bulk nonlinear media have been recently investigated both analytically and numerically [64]. The existence and stability of vortex solitons in a ring-shaped partially parity-time-symmetric potential have been studied in detail, revealing that robust nonlinear vortices can be easily created by input Gaussian beams with embedded vorticities [65].…”
Section: Introductionmentioning
confidence: 99%